2019
DOI: 10.3892/mmr.2019.10334
|View full text |Cite
|
Sign up to set email alerts
|

miR‑589‑5p is downregulated in prostate cancer and regulates tumor cell viability and metastasis by targeting CCL‑5

Abstract: Prostate cancer is one of the most common human malignancies, which represents a serious threat to health, and micrornas (mirnas/mirs) have been reported to be closely associated with the progression and development of prostate cancer. The present study aimed to investigate the expression patterns, functions and underlying mechanisms of mir-589-5p in prostate cancer. The results demonstrated that the expression levels of mir-589-5p were downregulated in prostate cancer tissues and cell lines. overexpression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…In present study, we unveiled miR-589-5p as the downstream miRNA sponged by LOXL1-AS1 in laryngocarcinoma. MiR-589-5p has been reported as important in suppressing the progression of hepatocellular carcinoma [25], endometrial cancer [26], prostate carcinoma [27], and non-small cell lung cancer [28]. Accordingly, our study also proved that miR-589-5p exerted a inhibitory function in laryngocarcinoma progression.…”
Section: Discussionsupporting
confidence: 75%
“…In present study, we unveiled miR-589-5p as the downstream miRNA sponged by LOXL1-AS1 in laryngocarcinoma. MiR-589-5p has been reported as important in suppressing the progression of hepatocellular carcinoma [25], endometrial cancer [26], prostate carcinoma [27], and non-small cell lung cancer [28]. Accordingly, our study also proved that miR-589-5p exerted a inhibitory function in laryngocarcinoma progression.…”
Section: Discussionsupporting
confidence: 75%
“…Nevertheless, the mechanism of CCL5 in prostate cancer has not been studied very well. Ji et al [29] demonstrated that miR-589-5p regulates prostate cancer cell viability and metastasis by targeting CCL-5. Xiang et al [30] showed that Infiltrating CD4+ T cells attenuate chemotherapy sensitivity in prostate cancer via CCL5 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…In the vast majority of human cancer types, miR-589-5p was reported to be down-regulated and function as a tumor-suppressive miRNA, including endometrial carcinoma [14], prostate cancer [15], non-small cell lung cancer [16] and acute myeloid leukemia [17]. However, in the HCC context, several lines of evidence have reported that miR-589-5p was remarkably upregulated in clinical HCC tissues, and overexpression of miR-589-5p signi cantly contributed to the progression and aggressiveness of HCC to varying mechanisms [11,12].…”
Section: Discussionmentioning
confidence: 99%